On Neutrosophic Γ-Semirings - Yella Bhargavi; Akbar Rezaei (Neutrosophic Sets and Systems, 2021)
In this paper, we introduce and study the concept of Neutrosophic Γ-semiring and study various properties. Also, we prove that there is a one-to-one correspondence between Neutrosophic Γ-semirings and sub Γ-semirings of a Γ-semiring. Further, we prove that the set of all neutrosophic Γ-semirings is a De-Morgan algebra. Moreover, we establish that the homomorphic image and inverse image of a Neutrosophic Γ-semiring is also a Neutrosophic Γ-semiring.